2017
DOI: 10.1083/jcb.201611168
|View full text |Cite
|
Sign up to set email alerts
|

ROS and glutathionylation balance cytoskeletal dynamics in neutrophil extracellular trap formation

Abstract: Neutrophils can release their genomic DNA as extracellular traps (NETs), which ensnare bacteria and limit their replication. Stojkov et al. find that modulation of cytoskeletal dynamics by reactive oxygen species and glutathionylation controls the degranulation and release of mitochondrial DNA required for NET formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 59 publications
11
127
0
Order By: Relevance
“…In the present study, we have addressed these standing questions in a model of freshly isolated human neutrophils. We found that different chemotactic peptides, including the key vascular chemokine CXCL1 and the end‐target chemoattractant fMLP, triggered very slow but robust MT polymerization in these leukocytes, consistent with recent studies on fMLP‐ and C5a‐triggered neutrophils . Using a probe of real‐time tubulin polymerization, SiR‐tubulin, we found that neutrophils elongated their MTs within minutes when encountering these chemotactic peptides at their soluble states.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the present study, we have addressed these standing questions in a model of freshly isolated human neutrophils. We found that different chemotactic peptides, including the key vascular chemokine CXCL1 and the end‐target chemoattractant fMLP, triggered very slow but robust MT polymerization in these leukocytes, consistent with recent studies on fMLP‐ and C5a‐triggered neutrophils . Using a probe of real‐time tubulin polymerization, SiR‐tubulin, we found that neutrophils elongated their MTs within minutes when encountering these chemotactic peptides at their soluble states.…”
Section: Introductionsupporting
confidence: 90%
“…So far, compounds with a selective ability to interfere with MT polymerization but not with preexistent MTs have not been extensively characterized. Taxol was recently shown to interfere with MT polymerization in neutrophils primed by GM‐CSF and subsequently stimulated with C5a, a process critically dependent on the production of reactive oxidation species (ROS) and on neutrophil NADPH oxidase activity . The present study is the first to show that taxol suppresses MT polymerization triggered by both CXCL1 and fMLP, key chemotactic peptides implicated in numerous neutrophil diapedesis and interstitial migration processes underlying neutrophil recruitment to sites of infection and injury .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…ROS induces actin and tubulin glutathionylation, which is tightly regulated by glutaredoxin 1 (Grx1), an enzyme required for deglutathionylation of actin and microtubulin. Thus, an intact cytoskeleton is required for the formation of NETs 6 . Moreover, optic atrophy 1 (OPA1), one of five GTPase dynamin family members, known to play a role in mitochondrial (mt) fusion, has recently been shown to be required for ATP production through glycolysis in neutrophils.…”
Section: Introductionmentioning
confidence: 99%